Prevalence of skin cancer based on skin biopsies in Bir hospital, Nepal (Journal of Pathology of Nepal, 2022)
Background: Cancer, one of the most dreaded non-communicable diseases has become an important contributor to the global burden of diseases. The incidence of skin cancer is rising. Clinical history, physical examination, laboratory investigations including biopsy are different modalities for the diagnosis of the disease. This study aimed to find the prevalence of skin cancer among patients visiting Bir hospital.Materials and Methods: This was a retrospective study carried out in the National Academy of Medical Science, Bir Hospital from Baishakh 1st 2071 to 30th Poush 2075. It included all the skin malignancies and pre-invasive lesions received and diagnosed in the Department of Pathology.Results: A total number of 1555 skin biopsies were obtained in the past five years where we diagnosed a total of 165 (10 %) cases as malignant which included the premalignant cases too. The most affected age group was 66 to 75 years (29 %) with 55% male and 45%females. Our data showed head and neck was the most common site occupying 67% of the total case followed by lower limbs 15%. Our study also revealed that 40% of malignant cases were basal cell carcinoma which was followed by squamous cell carcinoma comprised 36% and malignant melanoma(15%).Conclusions: In this study, basal cell carcinoma was the most common malignancy followed by squamous cell carcinoma and malignant melanoma. Head and neck was the most common site.